FDI and growth in Europe: the role of territorial capital - Laura Resmini; Laura Casi (European Regional Science Association (ERSA), 2012)
In the last years, and particularly since the publication of the famous Barca Report (Barca, 2009), the European Union (EU) is starting to acknowledge the importance of spatially targeted regional policies and to understand how crucial a territorial approach can be in order to achieve desirable social, economic and environmental outcomes. Indeed the increasing complexity in the path to regional growth and development is fostered by globalization and the creation of large integrated areas such as the European Union, where regions need to leverage their territorial capital to compete effectively. In this context we analyse the impact of FDI on growth and development of European regions, discussing the role of different components of territorial capital in determining the intensity and the direction of such an impact. In doing so we start from the assessment of the impact that various types of FDI can have according to the characteristics of the country they come from (Industrialized vs. emerging countries; European vs. non-European countries) and their sector's affiliation (i.e. low and high tech manufacturing sectors; business services vs. financial services, etc.). Then we inspect the possibility that such an impact may vary with the endowments of different type of territorial capital. In particular, the paper aims at answering to the following research questions: do different levels of agglomeration economies determine different additional FDI induced growth rates? How social capital influences the impact of FDI on the growth of a region? Does relational capital matter in the FDI-growth relationship? In order to answer these research questions, we analyse empirically the impact of different measures of FDI density on regional economic performance, measured as real GVA growth rate, exploiting FDIRegio database and Eurostat data. In order to mitigate possible endogeneity problems and non linearities in the relationship, we use different matching techniques and include various regional controls, such as human capital endowments, past growth rates and agglomeration trajectories, as well as demand and cost factors. Furthermore, in order to identify the territorial capital role in fostering the FDI-growth relationship, we allow such relationship to vary across different types of regions, grouped according to their economic specialization and social capital endowment. The latter is identified through a PCA analysis based on the results of the European Values Study, from the ZACAT - GESIS database
Keywords: 330